Different roles of axon guidance cues and patterned spontaneous activity in establishing receptive fields in the mouse superior colliculus - Liu, Mingna; Wang, Lupeng; Cang, Jianhua (Frontiers in Neural Circuits, 2014)
Visual neurons in the superior colliculus (SC) respond to both bright (On) and dark (off) stimuli in their receptive fields. This receptive field property is due to proper convergence of On- and Off- centered retinal ganglion cells to their target cells in the SC. In this study, we have compared the receptive field structure of individual SC neurons in two lines of mutant mice that are deficient in retinotopic mapping: the ephrin-A knockouts that lack important retinocollicular axonal guidance cues and the nAChR-β2 knockouts that have altered activity-dependent refinement of retinocollicular projections. We find that even though the receptive fields are much larger in the ephrin-A knockouts, their On-Off overlap remains unchanged. These neurons also display normal level of selectivity for stimulus direction and orientation. In contrast, the On-Off overlap is disrupted in the β2 knockouts. Together with the previous finding of disrupted direction and orientation selectivity in the β2 knockout mice, our results indicate that molecular guidance cues and activity-dependent processes play different roles in the development of receptive field properties in the SC.